2014
DOI: 10.1158/1078-0432.ccr-14-1138
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Mediates Radiation-Related Lymphopenia and Attenuates NSCLC Radiation Response

Abstract: Purpose Radiotherapy (RT) can result in lymphopenia, which has been linked to poorer survival. Here, we test the hypothesis that RT-induced lymphopenia is mediated by a tumor-secreted factor, Galectin-1 (Gal-1), which possesses T-cell pro-apoptotic activities. Experimental Design Matched Gal-1 wildtype or null mice were implanted with Lewis Lung carcinoma (LLC-1) that either expressed Gal-1 or had Gal-1 stably down-regulated. Tumors were irradiated locally and circulating Gal-1 and T-cells were measured. Tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…The risk of lymphopenia correlated with MLD. Kuo et al 19 showed a similar effect in a small study of patients with stage I-II NSCLC treated definitively with SABR.…”
mentioning
confidence: 74%
“…The risk of lymphopenia correlated with MLD. Kuo et al 19 showed a similar effect in a small study of patients with stage I-II NSCLC treated definitively with SABR.…”
mentioning
confidence: 74%
“…2) that irradiation induces lymphopenia through not only a direct effect on circulating lymphocytes, but also through indirect effect on circulating lymphocytes as well as an indirect effect on stem cells in the nonirradiated BM. Recently, induction of galectin-1 from cancer cells after irradiation has been shown to cause lymphopenia in mice (7). Similarly cytokines IL15 and IL7 were implicated to play a role in compensating lymphopenia induced by HIV infection and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Galectin-1 is enriched in the tumor-associated stroma or neovascular endothelium 16-19 . Radiation therapy/exposure has been shown to further augment galectin-1 expression in the tumor microenvironment 2,20,21 . The anti-angiogenic 33-amino acid, beta sheet peptide anginex 22,23 specifically binds and inhibits the function of galectin-1 receptor 16-19 .…”
Section: Introductionmentioning
confidence: 99%